2021
DOI: 10.3390/pharmaceutics13030390
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a TLR4 Agonist/Cationic Liposome Adjuvant on Varicella-Zoster Virus Glycoprotein E Vaccine Efficacy: Antigen Presentation, Uptake, and Delivery to Lymph Nodes

Abstract: Adjuvant CIA09, composed of 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP)-based cationic liposomes and the toll-like receptor 4 agonist de-O-acylated lipooligosaccharide (dLOS), has been shown to enhance antibody and cellular immune responses to varicella-zoster virus (VZV) glycoprotein E (gE), recombinant tuberculosis vaccine antigen, and inactivated Japanese encephalitis vaccine. In this study, we investigated its modes of action using VZV gE as a model antigen. Liposomes adsorbed gE and cooperatively wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Shingrix (GSK) is a recombinant subunit vaccine comprising a VZV gE expressed in CHO cells and the liposome-based adjuvant AS01 B . Other work has sought to investigate subunit vaccines against HZ using gE proteins generated from CHO or insect cells formulated with novel adjuvants (Cao et al, 2021;Lee et al, 2020;Luan et al, 2022a, Luan et al, 2022bWang et al, 2021;Wui et al, 2019;Wui et al, 2021). Here, we investigated and showed that the gE protein could be solubly expressed and purified from E. coli, and then formulated as a subunit vaccine candidate with an appropriate adjuvant to elicit not only a robust neutralizing titer but also a strong CMI response.…”
Section: Discussionmentioning
confidence: 99%
“…Shingrix (GSK) is a recombinant subunit vaccine comprising a VZV gE expressed in CHO cells and the liposome-based adjuvant AS01 B . Other work has sought to investigate subunit vaccines against HZ using gE proteins generated from CHO or insect cells formulated with novel adjuvants (Cao et al, 2021;Lee et al, 2020;Luan et al, 2022a, Luan et al, 2022bWang et al, 2021;Wui et al, 2019;Wui et al, 2021). Here, we investigated and showed that the gE protein could be solubly expressed and purified from E. coli, and then formulated as a subunit vaccine candidate with an appropriate adjuvant to elicit not only a robust neutralizing titer but also a strong CMI response.…”
Section: Discussionmentioning
confidence: 99%
“…dLOS-induced cytokine production in mouse peritoneal macrophages is comparable to MPLA but exhibits superior activation capabilities in human monocytes and DCs [ 114 ]. In preclinical animal studies, the adjuvant CIA09, comprising cationic liposomes and dLOS, effectively boosted antibody and cell-mediated immune responses against recombinant tuberculosis antigens, inactivated Japanese encephalitis vaccine (JEV), and recombinant varicella-zoster virus (VZV) glycoprotein E (gE) antigen [ 115 , 116 , 117 , 118 ].…”
Section: Enhancement Of Lbnp Vaccine Efficacy Via Toll-like Receptor ...mentioning
confidence: 99%
“… 42 , 64 Further, as a carrier of nanovaccine, cationic liposomes have been notably acknowledged for better cellular uptake, antigen delivery and DCs initiation. 40 , 65 They are well-known DCs inducers and enhance expression of CD40, CD80, and CD86, resulting in the presentation of class I antigen and priming of antigen-specific CD8+ T cells. 26 , 66
Figure 2.
…”
Section: Effect Of the Nanovaccines On Dcsmentioning
confidence: 99%